The cloning of the xylose isomerase gene (Xyla) from bacillus subtilis through oligonucleotide primers directed pcr amplification / Ho Wai Kuan, Chen Hooi Hooi and Kan Mun Seng - Ho, Wai Kuan; Chen, Hooi Hooi; Kan, Mun Seng (2006)
Xylose isomerase is also referred to as glucose isomerase. It reversibly catalyses the isomerisation reaction between D-xylose and D-xylulose, as well as D-glucose and D-fructose. Nucleotide sequences encoding the isomerases from various organisms are known. In our study, an isolate from soil sample that was pre-determined as Bacillus subtilis was used. Its genomic DNA was obtained through phenol chloroform extraction and alcohol precipitation. Purified genomic DNA was used as template in xylose isomerase gene (xyIA) amplification by polymerase chain reaction. Several sets of oligonucleotide primers were designed with reference to published nucleotide sequences and synthesised for the use ill gene amplification. The study results show successful xylA gene amplification after several attempts onto the optimisation of PCR protocols. Analysis by agarose gel electropheresis estimated the PCR amplified product to be -1.3 kb, is ill agreement to xylA published sequence, 1338 bp (NCBI GenelD: 939558). The product was further purified and endonucleases restricted by BamHI and Kpnl that both recognition sites were included in the forward and reverse primers respectively. Treated PCR product was subsequently ligated into pGEM-3Z clon in vector that has been BamHI/Kpnl restricted. DNA sequencing analysis of the cloned gene shows 72% homology ill comparison the published xylA gene, implies a variant of xylose isomerase gene has been cloned.